2015
DOI: 10.1111/hae.12617
|View full text |Cite
|
Sign up to set email alerts
|

Impact of severe haemophilia A on patients' health status: results from the guardian 1 clinical trial of turoctocog alfa (NovoEight®)

Abstract: Summary Haemophilia and its treatment interfere with patients' life and may affect adherence to treatment. This study explored the impact of severe haemophilia A on patients' health status, especially in young adults (YA), using data from guardian™ 1, a multinational, open‐label, non‐controlled phase 3 trial investigating safety and efficacy of turoctocog alfa (NovoEight®) in previously treated patients aged 12 years and older with severe haemophilia A (FVIII ≤ 1%). Health status was assessed using the EuroQoL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…While most studies investigated depression alone, six studies reported anxiety and depression without separating those affected by depression, anxiety or both . All six studies used the EuroQoL five dimension scale (EQ5D), and therefore, this resulted in low statistical heterogeneity among studies ( I 2 = 0%, P = .60).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While most studies investigated depression alone, six studies reported anxiety and depression without separating those affected by depression, anxiety or both . All six studies used the EuroQoL five dimension scale (EQ5D), and therefore, this resulted in low statistical heterogeneity among studies ( I 2 = 0%, P = .60).…”
Section: Resultsmentioning
confidence: 99%
“…Our search strategy identified 2315 studies, of which 28 studies met our eligibility criteria (Figure 1). Twenty‐seven studies had a cross‐sectional design, and one study was a retrospective chart review (Table 1). None of the studies were prospective in nature.…”
Section: Resultsmentioning
confidence: 99%
“…For the full analysis set of the trial as well as for the adults aged 30-60 years, the change from baseline in EQ-5D VAS did not differ according to the treatment regimen received within the 12 months preceding the trial [33]. In the young adults, as indicated in Figure 1, the baseline EQ-5D VAS was comparable between the group who had received prophylaxis and the group who had received on-demand prior to the trial; mean change in EQ-5D VAS from baseline to the end-of-treatment visit showed an improvement (no information on statistical significance available) for both groups, however the improvement was greater in the individuals previously treated with on-demand regimen before the trial (5.2 point improvement, SD = 10.3) than individuals previously treated with prophylaxis (1.2 point improvement, SD = 18.5).…”
Section: Young Adults May Particularly Benefit From the Switch To Promentioning
confidence: 94%
“…guardian 1 enabled the health status of young adults aged 16-29 years to be compared with both the full analysis set of the trial, and to the gender and agespecific reference values from the UK general population using data from the EQ-5D. Young adults (16-29 years, n = 83) and older adults (30-60 years, n = 51) with hemophilia A reported more problems in all EQ-5D domains and in particular for the Mobility and Pain/Discomfort domains than young adults and adults in the respective reference populations [33,34]. For all EQ-5D domains, adults 30-60 years of age reported more problems than young adults, supporting the degenerative nature of hemophilia.…”
Section: Young Adults May Particularly Benefit From the Switch To Promentioning
confidence: 99%
“…The most common manifestations of hemophilia are joint bleeds, leading to painful arthritis, limited joint mobility, and impaired physical functioning. As a result, PWH experience a reduced quality of life (QOL) [3-7]. …”
Section: Introductionmentioning
confidence: 99%